Development of Learning Based on Problems in Chemistry Subjects to Improve Students' Critical Thinking Ability: Pengembangan Pembelajaran Berdasarkan Masalah Pada Mata Kuliah Kimia Untuk Meningkatkan Kemampuan Berpikir Kritis Mahasiswa - Priska, Melania; Pendy, Agnes; Peni , Natalia; Carvallo, Ludovicus (Pedagogia : Jurnal Pendidikan, 2020)
Solution material is one of the materials that requires a student's level of understanding at the critical thinking level. Critical thinking skills train students to learn to find and solve problems using scientific methods based on real experiences encountered and experienced directly. To be able to find the concept of knowledge based on existing realities, an appropriate learning model is needed, namely a problem-based learning model. This study aims to determine students' critical thinking skills. The type and design of this research is development research with a nonequivalent control group design. The samples of this research were students of semester 2, Biology Education Study Program, University of Flores. This research was conducted from April-June 2020. Data were collected using the critical thinking ability test technique of students in the chemical solution subject, followed by processing and analyzing data using the prerequisite analysis test in the form of normality test, homogeneity test, and t-test. The data analysis shows the significance value of the normality and homogeneity test, namely α> 0.05, while for the t-test α <0.05. From these results prove that problem-based learning can improve students' critical thinking skills in chemistry subject matter solution